Jute in India - "Sarkar, Goutam K." (Calcutta, 1989)
The protracted jute imbroglio has focused great attention on this traditional agro-based industry of India which employs over 200 thousand workers and supports about four million families. This book presents for the first time the problems, prospects, and policy issues concerning the industry's manufacturing sector, as well as its agricultural counterparts. Although written in the Indian context, the volume provides international perspectives as well, which will interest those concerned with world jute economy in particular and commodity problems in general. Readership: economists, commodity specialists, general readers interested in jute industry
Keywords: Agriculture-economic aspects